1972
DOI: 10.1039/p19720000513
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the biosynthesis of steroids and terpenoids. Part VI. The sterols of yeast

Abstract: The minor sterol concentrates were the residues of the commercial production of ergosterol from S. cerevisiae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

1972
1972
1987
1987

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Yeasts of the genus Saccharomyces are particularly rich in sterols (69). Ergosterol has been identified as the major sterol in S. cerevisiae (6,25,76,101), Kluyvero-myces fragilis (234), and C. albicans (43), and can account for over 90% of the total sterol. Strain differences can, however, exist as shown by the major occurrence of ergosta-5,7,22,24(28)-tetraen-3f3-ol in S. cerevisiae N.C.Y.C.…”
Section: Stero +Digtyceridementioning
confidence: 99%
See 2 more Smart Citations
“…Yeasts of the genus Saccharomyces are particularly rich in sterols (69). Ergosterol has been identified as the major sterol in S. cerevisiae (6,25,76,101), Kluyvero-myces fragilis (234), and C. albicans (43), and can account for over 90% of the total sterol. Strain differences can, however, exist as shown by the major occurrence of ergosta-5,7,22,24(28)-tetraen-3f3-ol in S. cerevisiae N.C.Y.C.…”
Section: Stero +Digtyceridementioning
confidence: 99%
“…All the sterols named in Fig. 3 have been isolated from various S. cerevisiae strains and have been considered as possible biosynthetic intermediates by Barton and his co-workers (23)(24)(25). The efficiency with which cell-free extracts have been able to con-…”
Section: Stero +Digtyceridementioning
confidence: 99%
See 1 more Smart Citation
“…A detailed analysis of the fragmentation pattern is precluded by the complexity of the spectrum. However, the major fragments support the hypothesis that it is a C28 sterol (8)(9)(10): (14). A more definite assignment would require the separation of the components, which was not attempted because of the small quantities available.…”
mentioning
confidence: 75%
“…Recent studies involving the use of gas-liquid chromatography and mass spectrometry have revealed the presence of other sterols in significant quantities in flaccharomyees cerevisiae (LONOLEY et al 1968, HUNTER and ROSE 1972, BARTON et al 1972) but the present authors have found that in Kluyveromyces fragilis only ergosterol is detectable (PENMAN and DUFFUS 1974). Because of the relative paucity of knowledge concerning the flux of lipid components during the cell cycle, it seemed of interest to examine the accumulation of this sterol fraction during the cell cycle in K .…”
mentioning
confidence: 90%